1994
DOI: 10.1063/1.112932
|View full text |Cite
|
Sign up to set email alerts
|

Shock wave and plasma dynamics in a surface discharge flash lamp

Abstract: Shock waves and plasma dynamics induced by an open discharge called a ‘‘formed-ferrite-plasma’’ source result in intense radiation from the visible to the vacuum ultraviolet region. An experimental study of both the shock waves and plasma expansions from the ferrite surface has been carried out as a function of electrical energy deposition and of background argon pressure. We show that the propagation of the shock wave is accurately described by the following expression: R=b(E/ρ0)αtn, where R is the distance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…To measure the pressure in the hot superheated water filament more directly, we have monitored micro shock waves in air that originate from the irradiated microjet for the same internal energy as detailed above (Figure ). The increasing radius of the shock wave (SFR) is plotted against time, and an expression SFR( t ) = A ( E ) t x , with A = 8.5 ± 1.1 and x = 0.67 ± 0.01, is fitted to the data (Figure ). , From these data an initial shock wave velocity can be determined to be close to 2000 m s -1 . It has been shown that strong shock waves enable the determination of the equation of state (EOS) of water for extreme temperatures and pressures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure the pressure in the hot superheated water filament more directly, we have monitored micro shock waves in air that originate from the irradiated microjet for the same internal energy as detailed above (Figure ). The increasing radius of the shock wave (SFR) is plotted against time, and an expression SFR( t ) = A ( E ) t x , with A = 8.5 ± 1.1 and x = 0.67 ± 0.01, is fitted to the data (Figure ). , From these data an initial shock wave velocity can be determined to be close to 2000 m s -1 . It has been shown that strong shock waves enable the determination of the equation of state (EOS) of water for extreme temperatures and pressures.…”
Section: Resultsmentioning
confidence: 99%
“…The increasing radius of the shock wave (SFR) is plotted against time, and an expression SFR(t) ) A(E)t x , with A ) 8.5 ( 1.1 and x ) 0.67 ( 0.01, is fitted to the data ( Figure 6). 59,60 From these data an initial shock wave velocity can be determined to be close to 2000 m s -1 . It has been shown that strong shock waves enable the determination of the equation of state (EOS) of water for extreme temperatures and pressures.…”
Section: A Oh-stretch Mode As a Probe Of Hydrogen-bondmentioning
confidence: 99%
“…In particular, it has been shown [12] that the use of plasma electrodes in the volume discharge of a CO 2 laser shock wave heats the volume of the laser and limits the frequency of the generated laser radiation. The interval between pulses had to be increased [13,14]-shock waves from pulsed discharges limit the use of the volume discharge as a light source [15][16][17][18]. On the other hand, high-energy discharges of short duration can be sources of intensive controlled shock waves and may be used for various applications.…”
Section: Introductionmentioning
confidence: 99%